Development scenario in Nepal has not changed fundamentally - Whelpton, John (Journey for Sustainable Development and Peace Journal, 2025)
My book (A History of Nepal) covered the period up to 2004. It was a general history of Nepal so included a lot on economic issues but I am not a development economist so was essentially just trying to synthesize what people with more expertise in that field were saying. Tentatively, I would say that despite the radical political changes since 2004, the development scenario has not changed fundamentally.